Development and characterization of a surfactant responsive to redox conditions for gas recovery in foam drainage - Jia Li; Ming Wen; Zeyin Jiang; Long Xian; Jiawen Liu; Juan Chen (Scientific Reports)
Abstract To address the challenge of reusing foaming agents in foam drainage gas production processes, we developed a redox-responsive surfactant with a straightforward preparation method based on molecular electrostatic interaction assembly. The redox response mechanism of the surfactant was investigated through surface tension, absorbance, particle size, and Zeta potential analyses. Results indicate that the minimum surface tension in the oxidized state can reach 26.4 mN∙m-1, and even after 6 repetitions, it remains at 28 mN∙m-1. In the oxidized state, the surfactant’s particle size can reach 310 nm, effectively stabilizing foam by reducing the liquid discharge rate of the liquid film through large micelles. Moreover, oxidized surfactants exhibit excellent dispersion and stability properties, with a Zeta potential of 28.7 mV. Even after 6 repetitions, the Zeta potential remains above 27.1 mV. Foaming performance tests demonstrate that the oxidation-reduction surfactant exhibits favorable foaming, stabilizing, and reusing effects. At 90 ℃, the initial and 5-minute foaming heights reached 131 mm and 94 mm, respectively. After 6 repetitions, these heights were 124 mm and 85 mm, respectively. The successful development of this treatment agent can effectively address on-site foam drainage needs and reduce the operational costs associated with foam drainage.